Berel Kurgans within the Context of Funeral Rites / Ölü Gömme Gelenekleri Bağlamında Berel Kurganları - Mehmet Kutlu*; Leila Kutlu** (Uluslararasi Kibris Universitesi Fen-Edebiyat Fakultesi, 2021)
Permafrost layers under the stone kurgans at Berel Valley located at the southwestern slopes of Altai Mountains, was initially discovered by Wilhelm Radloff in 1865. It had been revealed that there was a deep pit with the burial chambers made of timbers at the center of a kurgan with permafrost layers. Burial chambers, where wooden sarcophagus carved from a single piece of log were placed, had also contained human remains and many horse burials. However, the human and horse burials could not be preserved due to the insufficient technological and methodological conditions in excavation and protection of the findings at that time. Berel Kurgans had not extensively excavated and studied for nearly 150 years until Prof. Zainolla Samashev leading East Kazakhstan Archeological Expedition, initiated large-scale excavations at Berel in 1998. As a result, permafrost layers were detected in the 10th and 11th kurgans. Organic artifacts along with the remains of human beings and horses that cannot be preserved in ordinary kurgans reached nowadays and provided an opportunity to examine them. The purpose of the current research is to examine the kurgans of the Scythian, Hsiung-nu, Xianbei and Turkic khaganate periods in the Berel within the context of burial rites and customs. Some similarities in burial rites determined as a result of anthropological evaluations presents evidence of cultural continuity from the Scythian to the Turkic khaganate periods.